Visualising climate change narratives: a comparative analysis of framing strategies on AlMamlaka TV and Jordan TV - Aljalabneh, Abd Allah (Frontiers in Communication, 2025)
IntroductionClimate change disproportionately impacts developing nations by exacerbating existing vulnerabilities and intensifying extreme weather events, posing significant socio-economic and environmental challenges. This study investigates the framing strategies utilised by two prominent Jordanian television broadcasters, namely AlMamlaka TV and Jordan TV, to shape public perceptions of climate change.MethodsThe study employs a convergent parallel mixed-methods design that integrates quantitative visual content analysis with qualitative inductive thematic analysis. The study examined a total of 108 video clips related to climate change, published by the official YouTube channels of the two broadcasters during 2023. The quantitative analysis focused on the frequency of visual imagery, tone, guest representation, and framing categories. In parallel, a qualitative component was undertaken to explore the symbolic dimensions, affective cues, and editorial logics embedded in the media narratives.ResultsThe analysis suggests that both channels tended to adopt problem-oriented frames; however, AlMamlaka TV appeared to place greater emphasis on solutions-focused narratives, expert commentary, and emotionally resonant imagery. In contrast, Jordan TV maintained a more neutral and fact-driven approach. Their coverage emphasises governmental perspectives and local impacts. These variations highlight divergent institutional strategies and their implications for audience engagement.DiscussionThe findings illustrate the complex role of media institutions in mediating climate change discourse within the Jordanian context. The differences between AlMamlaka TV and Jordan TV indicate how editorial policies and institutional identities shape framing practices. This has broader implications for how audiences interpret climate risks and possible responses. Moreover, these results suggest that the presence of solutions-oriented narratives may enhance public trust and engagement with climate communication.